On the essay in a time of GenAI - Corbin, Thomas; Walton, Jack; Bannister, Peter; Deranty, Jean-Philipe (Taylor & Francis, 2025)
The essay is facing a legitimacy crisis. With students increasingly able to generate plausible submissions using Generative AI, the essay’s status as a valid instrument of assessment of student learning is under serious threat. Yet, rather than abandoning the essay or turning to superficial fixes, this paper argues that the current disruption offers a chance to reconsider what essays are for as well as the chance to consider what they could be. In this paper, we distinguish between the standardised academic essay of today from the historically contextualised essay. Drawing from the history of ideas, we argue that essays are best understood not as products to be measured against static criteria, but exploratory engagements with thought, shaped by uncertainty, divergence, and the recursive relationship between writer and text. This understanding has long been at odds with how essays are typically assessed and it is this misalignment, not AI alone, that we suggest underpins the current crisis. In response, we propose a set of structural changes to essay assessment design. We propose a holistic approach to assessment which, we suggest, helps show how the essay can be reconfigured as both an educationally meaningful and valid assessment task, fit for an age of AI without being defined by it.
Keywords: generative artificial intelligence; essay; academic writing; philosophy of education; assessment